106k views
4 votes
What is the value of the expression

(−3^2/3^3)2
when it is simplified?
Enter your answer as the correct value.

User Solace
by
5.4k points

2 Answers

1 vote

So either you meant
((-3^2)/(-3^3) )*(2)/(1), or you actually meant
((-3^2)/(-3^3) )^2 . I'll solve both.




((-3^2)/(-3^3) )*(2)/(1)


Firstly, do the division. Since the numerator and the denominator have the same base, you can write it as -3^-1, which can be rewritten as -1/3.
-(1)/(3)*(2)/(1)


Next, multiply the fractions, and your answer should be
-(2)/(3)




((-3^2)/(-3^3) )^2


Firstly, multiply square with the powers in the fraction to get
(-3^4)/(-3^6)


Next, divide. Like before, they have the same base, so the answer can be written as -3^-2, which can be rewritten as 1/3^2 = 1/9.

User UbiQue
by
6.1k points
3 votes


(-(3^2)/(3^3) )^2 = (-(1)/(3) )^2 = (1)/(9)


OR (in more details):



(-(3^2)/(3^3) )^2 = (-3^(2-3))^2 = (-3^(-1))^2 = (-(1)/(3) )^2 = (1)/(9)


User Toph
by
5.4k points